Role of 1.5% acetic acid irrigation and medical management in chronic persistent suppurative otitis media - Kanakarajulu, Bhavya; Sowmya, Lanke; ., Teja (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic ear discharge in chronic suppurative otitis media (CSOM) persisting for more than two weeks has become difficult to treat for ENT specialists due to resistance to the available antibiotics and patient's affordability for its cost. Also, biofilms have been responsible for the disease and cause tympanic membrane perforation and deafness. The use of 1.5% acetic acid irrigation acts as an antiseptic, and altering the middle ear's pH to treat otorrhea in CSOM needs to be studied. Aim of the study to assess results of 1.5% acetic acid irrigation and topical and systemic antibiotic in CSOM and to consider the most appropriate medical management Methods: A total of 100 patients of CSOM was divided equally into two groups. Group 1 patients were treated with 1.5% acetic acid irrigation every other day, and group 2 was treated with topical and systemic antibiotics three drops’ times daily. Follow up of both groups every week up to symptomatic relief. Results: Otorrhoea resolution in the group treated with acetic acid was 88%, and healing of perforation was noted in 28 %, while the failure rate of 12%. Conclusions: Medical management of persistent CSOM with tubotympanic type by frequent aural cleaning, 1.5% acetic acid irrigation can be the more desirable choice than the topical and oral antibiotics. It is safe without any side effects and economical. Alteration of ear canal PH is one of the main factors for healing, in addition to mechanical disruption of biofilm and removal of deep-seated debris.